Dimensions of Occlusoproximal Cavitated Carious Lesions as a Cut-Off Point for Restorative Decision in Primary Teeth - Helena Scherer; Cleber Paradzinski Cavalheiro; José Carlos Pettorossi Imparato; Rachel de Oliveira Rocha; Fernanda Ruffo Ortiz; Tathiane Larissa Lenzi (Association of Support to Oral Health Research (APESB), 2023)
Objective: To investigate whether the dimensions of cavitated dentin carious lesions on the occlusoproximal surfaces of primary teeth could predict the location of cement-enamel junction (CEJ). Material and Methods: Two hundred extracted primary molars were selected and digital images were obtained. The teeth were set in arch models for clinical measurement. The cervical-occlusal (CO) and buccal-lingual/palatal (BL/P) cavities' dimensions were obtained by digital (Image J) and clinical (periodontal millimeter probe) assessments. The cervical margin location was also determined. The thresholds (cut-off points) were determined by sensitivity, specificity and the areas under the receiver operating characteristics curves (Az) for the two methods. Pearson's correlation coefficient was used to investigate the correlation between clinical and digital measurements. Logistic regression analysis was performed to evaluate the association between the dimensions and cervical margin location. Results: There was a strong correlation between methods for all measurements (CO: r=0.90, VL/P: r=0.95). Cavities with BL/P distance higher than 4.5 mm and CO dimension higher than 3.5 mm had a lower chance of presenting the cervical limit above the CEJ, irrespective of the measurement method. Conclusion: CO and VL/P dimensions could be used to predict the CEJ location and, ultimately, as a clinical parameter for restorative decision-making.